Effect Of Progressive Muscle Relaxation And Deep Breathing On Anxiety And Quality Of Life In Patients Covid-19 - Pratiwi Christa Simarmata; Hariati .; Fahliani Dwi Armarin (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
The Covid-19 disease that was detected at the end of 2019 quickly caused a pandemic, and became a global health issue. Progressive Muscle Relaxation (PMR) and Deep Breathing (DB) are exercises that can reduce blood pressure, heart rate, stress, lactic acid production, anxiety and pain. The purpose of the study was to assess the effect of PMR and DB on anxiety (anxiety) and quality of life (quality of life) of COVID-19 patients. The research design used a quasi-experimental with pretest and posttest with the control group. The research was conducted at Grandmed Lubuk Pakam Hospital. The sampling technique used purposive sampling, with a sample of 28 people, with 14 people in each group. Data were analyzed using paired t test. The procedure was carried out with 30 minutes of treatment every day for 5 consecutive days. There was a significant effect between the mean anxiety score before 43.08 (SD ±4.22) and after treatment 45.67 (SD ±2.41) and Quality of Life before 24.43 (SD±4.58) and after treatment 26.07 (SD ±3.58). The results of the difference in mean obtained p value = 0.00 on anxiety, and p = 0.01 on quality of life, or p value < 0.05. The results of the study concluded that there was a significant difference in the average difference between the PMR and DB intervention groups in reducing anxiety and increasing quality of life in Covid-19 patients. It is recommended for nurses to make PMR and DB one of the independent nursing interventions in providing nursing care to Covid-19 patients.